2015
DOI: 10.1007/s10560-015-0403-7
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Operationalization of Intensive Family Case Management: A Delphi Study

Abstract: Few evidence-based methods for case management in child protection and child welfare are available. That is why Youth Protection Amsterdam Area developed a new method, by integrating their best practices: Intensive Family Case Management (IFCM). Because IFCM was developed in practice, clarity about its core elements and behavior acts was lacking. The purpose of this study was to establish a valid operationalization of IFCM used for implementation purposes such as training, clinical supervision and monitoring. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 15 publications
0
19
0
2
Order By: Relevance
“…When the goals in the care plan are achieved, the child welfare worker prepares the family for case closure. Although the child welfare worker is responsible for all phases, collaboration with the family and, if present, with the extended social network is an important element of the method (Busschers & Boendermaker, et al, 2016). Families randomly assigned to the control group (from now on referred to as CAU-group) received only IFCM.…”
Section: Conditionsmentioning
confidence: 99%
“…When the goals in the care plan are achieved, the child welfare worker prepares the family for case closure. Although the child welfare worker is responsible for all phases, collaboration with the family and, if present, with the extended social network is an important element of the method (Busschers & Boendermaker, et al, 2016). Families randomly assigned to the control group (from now on referred to as CAU-group) received only IFCM.…”
Section: Conditionsmentioning
confidence: 99%
“…Following the expert Delphi study of Busschers et al (2016), this article further articulates the emergent organizational vision of IFCM, now following a bottom-up approach. By comparing both studies, we see how dynamic a continuous process of visioning can be.…”
Section: Discussionmentioning
confidence: 99%
“…Early in the visioning process, Busschers et al (2016) identified the core elements of the IFCM vision at CYPSA at three levels, based on an expert Delphi study:…”
Section: Case Descriptionmentioning
confidence: 99%
“…After referral to the child welfare agency, the FGC-group as well as the CAU-group were assigned to a child welfare worker and received Intensive Family Case Management (IFCM) [ 14 ], a supervision and case management method, based on Functional Family Parole Services (FFPS) [ 15 , 16 ], for engaging, motivating and working with high-risk youth and multi-problem families. In the first 6 weeks, the child welfare worker established a collaboration with the parents.…”
Section: Methodsmentioning
confidence: 99%